Craft-Therapy Hub: Pemberdayaan Ekonomi Kreatif dan Digitalisasi Usaha Anggota Prolanis - Injilia W.G Wua; Francisca Anggun Therok; Durand Fernandito; Lidya D.P Canon; Imam Santoso (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to empower 25 members of the Chronic Disease Management Program (Prolanis) at Puskesmas Bailang, Manado—primarily patients with type 2 diabetes mellitus and hypertension—through an integrated program called the "Craft-Therapy Hub." The program integrates craft therapy, creative economy empowerment, and business digitalization based on productive behavior. The implementation method utilized active learning, comprising seminars, craft therapy workshops, digital marketing simulations, and Focus Group Discussions (FGD). Participants were trained to create marketable crafts, such as bead jewelry and recycled decorations, serving a dual purpose as psychological therapy and entrepreneurial opportunities. Furthermore, participants practiced marketing their products digitally via WhatsApp Business and Instagram. Qualitative evaluation indicated an increase in participants' understanding of productive behavior, creative entrepreneurship, and basic digital marketing. The program resulted in the formation of five creative business groups equipped with initial business plans. This activity successfully serves as a model for health-based economic empowerment, combining therapeutic and entrepreneurial approaches for individuals managing chronic diseases.